Regulations of possible unfair competition in the field of meat and ways of their improvement within the EEU - Aleksanyan, Vardan; Hovhannisyan, Davit (Bulletin of Yerevan University G: Economics, 2021)
Unfair competition is prohibited in all countries having law on competition protection. It is also prohibited by the legislation of the member states of Eurasian Union. Public Misleading is one of the manifestations of unfair competition, but the behavior of companies is not always intentional. Sometimes such behavior is the result of incorrect regulation or legal misinterpretations. Studies on the turnover of "Sausages" and "hot dog" products in the field of meat show that EEU by-laws regulating the current sphere and its Armenian version contain a number of problems and inconsistencies, which can cause to consumers’ misleading and be considered as manifestations of unfair competition. Therefore, clarifications and changes should be made to avoid such negative consequences.